Using Medicare Data to Estimate the Prevalence of Breast Cancer Screening in Older Women: Comparison of Different Methods to Identify Screening Mammograms - Randolph, Whitney M; Mahnken, Jonathan D; Goodwin, James S; Freeman, Jean L (Health services research, 2002)
Objectives. To compare different methods for defining screening mammograms with Medicare claims and their impact on estimates of breast cancer screening rates. Methods. Medicare outpatient facility and physician claims for 61,962 women in 1993 and 59,652 women in 1998 were reviewed for evidence of receipt of screening mammography. We compared the estimates of screening mammography use derived from CPT (Current Procedure Terminology) codes to categorize mammograms as screening or diagnostic versus using an algorithm that uses CPT codes plus breast‐related diagnoses in the prior two years. We also compared estimates obtained from review of physician claims alone, facility claims alone, or the combination of the two sources of claims. Results. Use of physician claims alone produced estimates of screening rates similar to rates calculated from use of both physician and outpatient (facility) claims. In 1993, the CPT code for screening mammography underestimated the rate of screening compared to estimates generated by using the algorithm (8.3 percent versus 18.0 percent prevalence, p<0.001). By 1998, the screening prevalence rate generated from using the CPT code for screening mammography more closely approximated the rate generated by the algorithm (23.0 percent versus 25.1 percent). By all methods of estimating screening mammography with Medicare claims, its prevalence increased substantially between 1993 and 1998. Conclusion. Providers increased their use of the screening mammography code in their charges to Medicare during the 1990s. This has improved the claims' ability to distinguish screening from diagnostic mammograms, but screening rates computed with claims continue to fall below those generated from self‐reports of mammography use among general populations of older women.